Land Arrangement with the Theme of Bioclimatic Architecture at the Durian Fruit Agrotourism Development Center in Ngoro District, Jombang Regency, East Java - Syarifudin, Syahrian Najma Alif; W, Wiwik Widyo; Oktafiana, Brina (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
Ngoro Subdistrict is an area with potential in the development of Agrotourism in Jombang Regency. which is famous for its agricultural products in the form of superior durian fruit, and is one of the largest durian fruit production areas in East Java. Ngoro Subdistrict has an area of 49.86 km² which is dominated by rice fields (42%), followed by settlements (19%), forests (18%), moor (12%), and others. The soil conditions in the area are textured with napal sand loam or belong to the type of soil in the reddish-brown and lysotol mediteran complexes, where this soil condition is very suitable for planting plantations. The agro-tourism land arrangement in Ngoro District is designed in such a way with a land order that has natural nuances and is also creative. The orientation of the building mass and the laying of vegetation on the site are also considered to form a microclimate as well as support thermal comfort through passive shading and cooling, as well as being an accommodating area in various educational and tourist activities. Bioclimatic architecture has been applied to the design of land orders, namely conditioning the environment and adapting climate as well as human behavior in the interaction between humans and the environment. It is hoped that in the future it can provide benefits for the local community as well as the environment, aiming that local and domestic tourists can also enjoy the facilities in this agro-tourism. On the other hand, the design of durian fruit agrotourism in Ngoro is also to encourage and increase the income and welfare of the people in the area.Keywords: Ngoro Subdistrict; Jombang; Land Order; Bioclimatic; Agrotourism.